MURCS Association with Partial Duplication of the Distal Long Chromosome 5 and Unilateral Ovarian Agenesis - Anna Dabkowska-Huc; Piotr Skalba; Antoni Pyrkosz (Case Reports in Genetics)
A combination of the congenital abnormalities, Müllerian duct aplasia, renal aplasia, and cervicothoracic somite dysplasia, is defined as the MURCS association. Various genetic defects have been described in the MURCS association so far, yet the unambiguous molecular basis of these disorders has not been established. We report the case of an 18-year-old woman who presented with primary amenorrhea, right kidney, Arnold-Chiari malformation, and Klippel-Feil syndrome. In addition, the patient showed the following unusual features: right ovarian and Skenes gland agenesis, cubitus valgus with hyperextension and decreased range of motion at elbows, and facial changes. Moreover, the performed DNA analysis showed interstitial duplication in chromosome 5 (5q35.1). In the duplicated region, there are genes whose function is not well known. It is thought that they have an influence on the early stages of development and their joining in the later period can lead to neoplastic disorders, especially leukemias.